Current Ethanol Production Requirements for the Yeast Saccharomyces cerevisiae - da Silva Fernandes, Flávia; de Souza, Érica Simplício; Carneiro, Lívia Melo; Alves Silva, João Paulo; de Souza, João Vicente Braga; da Silva Batista, Jacqueline (International Journal of Microbiology, 2022)
An increase in global energy demand has caused oil prices to reach record levels in recent times. High oil prices together with concerns over CO2 emissions have resulted in renewed interest in renewable energy. Nowadays, ethanol is the principal renewable biofuel. However, the industrial need for increased productivity, wider substrate range utilization, and the production of novel compounds leads to renewed interest in further extending the use of current industrial strains by exploiting the immense, and still unknown, potential of natural yeast strains. This review seeks to answer the following questions: (a) which characteristics should S. cerevisiae have for the current production of first- and second-generation ethanol? (b) Why are alcohol-tolerance and thermo-tolerance characteristics required? (c) Which genes are related to these characteristics? (d) What are the advances that can be achieved with the isolation of new organisms from the environment?